Conflicts in Interreligious Education Exploring Theory and Practice - Kraml, Martina (De Gruyter, 2022)
Whenever people from different cultural and religious backgrounds converge, it produces tension and ambivalence. This study delves into conflicts in interreligious educational processes in both theory and practice, presenting the results of empirical research conducted at schools and universities and formulating ground-breaking practical perspectives for interreligious collaboration in various religious-pedagogical settings.